1983
DOI: 10.1111/j.1476-5381.1983.tb10002.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of postsynaptic α‐adrenoceptors in rat aortic strips and portal veins

Abstract: 1 Postsynaptic a-adrenoceptors in rat isolated aortic strips and portal veins have been examined using a number of agonist and antagonist drugs which have varying selectivity for a1-and a2-adrenoceptors. 4 In portal veins, the order of potency of the antagonists was prazosin> BE2254 > phentolamine > yohimbine > rauwolscine, again indicating an al-type of receptor. 5 The mean pA2 value for yohimbine was not significantly different in either tissue. However, mean pA2 values for prazosin, BE-2254 and phentolamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
20
2
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 30 publications
10
20
2
3
Order By: Relevance
“…Based upon the reported selectivity of the yohimbine diastereoisomers corynanthine and rauwolscine for a,-and a2-adrenoceptors, respectively (McGrath, 1982), our observations with these antagonists appear to confirm the view that the rat aorta contains only a,-adrenoceptors (Digges & Summers, 1983b), while the rabbit saphenous vein contains predominantly x2-adrenoceptors (Alabaster et al, 1985). The possible contribution ofa,-adrenoceptors to responses in the rabbit saphenous vein, as evidenced by the nonlinearity ofthe Schild plots for rauwolscine, appears to be minimal since the selective x,-adrenoceptor agonist McGrath, 1982) was markedly less potent than NA.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Based upon the reported selectivity of the yohimbine diastereoisomers corynanthine and rauwolscine for a,-and a2-adrenoceptors, respectively (McGrath, 1982), our observations with these antagonists appear to confirm the view that the rat aorta contains only a,-adrenoceptors (Digges & Summers, 1983b), while the rabbit saphenous vein contains predominantly x2-adrenoceptors (Alabaster et al, 1985). The possible contribution ofa,-adrenoceptors to responses in the rabbit saphenous vein, as evidenced by the nonlinearity ofthe Schild plots for rauwolscine, appears to be minimal since the selective x,-adrenoceptor agonist McGrath, 1982) was markedly less potent than NA.…”
Section: Discussionsupporting
confidence: 70%
“…The pA2 values for the selective m,-antagonist corynanthine against NA of 7.74 or (-)-m-octopamine of 7.49 are similar in separate studies of rat aorta (7.35 for NA, Digges & Summers, 1983b) and anococcygeus (7.3 for NA, McGrath, 1984). This validates the use of the aorta and confirms that for phenylethanolamines its ml-adrenoceptor need not be considered unusual.…”
Section: Discussionsupporting
confidence: 63%
“…Ikunobu et al, (1990) [17] found that, yohimbine inhibited the blood vessels responses to adrenaline and phenylephrine. Moreover, yohimbine was found not significantly different than prazosin (a selective α 1 adrenoceptor antagonist) in inhibiting the effects of phenylephrine and noradrenaline on rat aortic strips [26].…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity of clonidine, as judged by pharmacological and radioligand binding studies led Ruffolo et al (1980) and Weiss et al (1983) to conclude that the rat aorta and tail artery contained c2-adrenoceptors. Other studies with rat aortic strips concluded that it contained a2-adrenoceptors although more than one subclass of a1-adrenoceptors may be present (Digges & Summers, 1983;Randriantsoa et al, 1981;Beckenringh et al, 1983). Thus, in view of the difficulty of demonstrating the presence of the two subtypes of a-adrenoceptors in vitro, it may be premature to attribute with certainty the responses of isolated aortic and carotid strips in this study to the activation of either al or o2-adrenoceptors.…”
Section: (C) Responses In Calcium-free Solution (Cfs)mentioning
confidence: 99%